Labelled loans and human capital investments - Britta Augsburg; Bet Caeyers; Sara Giunti; Bansi Malde; Susanna Smets (Institute for Fiscal Studies (IFS), 2020)
Making lumpy human capital investments is difficult, particularly since returns may accrue with a significant time lag. Lack of commitment impedes savings and diverts funds from intended investments. We draw on a cluster randomised controlled trial in rural India to provide the first evidence that labelled microcredit is effective in increasing take-up of a lumpy human capital investment, a safe toilet. Testing predictions from a theoretical model provides novel evidence that loan labels influence household borrowing and investment decisions. Not all loans are used for sanitation investments, suggesting that loan labels offer a soft commitment incentive.
Keywords: O16; D14; G41; I12; 330; Bildungsinvestition; Ländliche Entwicklung; Mikrofinanzierung; Indien